The Madrasah Orangtua Program in Fostering a Rabbani Generation: A Case Study of Markaz Al Kautsar Magelang - Pamungkas, Septyayu Catur; Albab, Muhammad Ulil (ISLAMIKA, 2026)
Empirical studies on structured parental education programs in Islamic educational institutions remain limited, particularly regarding their role in systematically fostering a rabbani generation. This study aims to analyze the contribution of the Madrasah Orangtua Program to the development of a rabbani generation through parental capacity-building, Islamic parenting practices, and synchronization between home and madrasah. Using a qualitative descriptive approach supported by quantitative data, the research was conducted at Markaz Al Kautsar Magelang with program managers, teachers, and parents participating in the Madrasah Orangtua Program selected through purposive sampling. Data were collected through in-depth interviews, observations, documentation, and before–after questionnaires, then analyzed using thematic analysis and descriptive statistics. The findings indicate that the program strengthens parents’ roles and participation, improves Qur’an-based and prophetic parenting practices, enhances home–school alignment, and reinforces students’ religious conduct, character, emotional stability, and spirituality. These changes are reflected in increased levels of faith, noble character, religious understanding, and Islamic life orientation. The study implies that structured and continuous parental education constitutes a key foundation for building an integrated family–school educational ecosystem and provides an empirically grounded model for Islamic educational institutions seeking to strengthen character and spiritual development through parental engagement. It contributes to Islamic education discourse by positioning parenting education as a strategic pillar for nurturing a rabbani generation through systematic family–school collaboration.